Prevalence and Prognostic Importance of Pulmonary Hypertension in Dogs with Myxomatous Mitral Valve Disease. (March 2015) - Borgarelli, M.; Abbott, J.; Braz‐Ruivo, L.; Chiavegato, D.; Crosara, S.; Lamb, K.; Ljungvall, I.; Poggi, M.; Santilli, R.A.; Haggstrom, J.
Abstract : Background: Pulmonary hypertension (PH) is common in dogs with myxomatous mitral valve disease (MMVD) but its effect on clinical outcome has not been investigated. Hypothesis/objectives: The presence of PH worsens the outcome in dogs with MMVD. To compare survival times of dogs with MMVD and PH to those without PH. Animals: Two hundred and twelve client‐owned dogs. Methods: Case review study. Medical records of dogs diagnosed with ACVIM stage B2 and C MMVD between January 2010 and December 2011 were retrospectively reviewed. Long‐term outcome was determined by telephone interview or from the medical record. End of the observation period was March 2013. PH was identified if tricuspid regurgitation peak velocity was >3 m/s. Results: Two hundred and twelve were identified. Eighty‐three dogs (39%) had PH. PH was more commonly identified in stage C compared to B2 ( P < .0001). One hundred and five (49.5%) dogs died during the observation period. Median survival time for the entire study population was 567 days (95% CI 512–743). Stage C ( P = .003), the presence of PH ( P = .009), left atrial to aortic root ratio (LA/Ao) >1.7 ( P = .0002), normalized left‐ventricular end‐diastolic diameter (LVEDn) >1.73 ( P = .048), and tricuspid regurgitation pressure gradient (TRPG) >55 mmHg ( P = .009) were associated with worse outcomes in the univariate analyses. The presence of TRPG >55 mmHg (HR 1.8 95% CI 1–2.9; P = .05) and LA/Ao > 1.7 (HR 2 95% CI 1.2–3.4; P = .01) remained significant predictors of worse outcome in the multivariate analysis. Conclusions and Clinical Importance: In dogs with MMVD, moderate to severe PH worsens outcome.